2000
DOI: 10.1007/s002689910045
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Perforated Peptic Ulcer: Incidence, Etiology, Treatment, and Prognosis

Abstract: After increasing steeply at the beginning of the twentieth century, ulcer perforation incidence during the last decades has declined in the young and in men, and it has risen among the elderly and in women. These changes can be attributed to a cohort phenomenon: Ulcer perforation risk is particularly common in the cohorts born after the turn of the twentieth century and is less common in previous and succeeding birth cohorts. A decline in total incidence is expected with the death of the high risk cohorts. Mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
173
0
10

Year Published

2006
2006
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(188 citation statements)
references
References 52 publications
(88 reference statements)
5
173
0
10
Order By: Relevance
“…Heart and renal disease were excluded from the Charlson Index when stratified by this variable. tor for both peptic ulcer complications (18). Unfortunately, it was not possible to obtain valid information on the duration from symptom onset to initiation of treatment in this study.…”
Section: Peptic Ulcer Perforationmentioning
confidence: 99%
“…Heart and renal disease were excluded from the Charlson Index when stratified by this variable. tor for both peptic ulcer complications (18). Unfortunately, it was not possible to obtain valid information on the duration from symptom onset to initiation of treatment in this study.…”
Section: Peptic Ulcer Perforationmentioning
confidence: 99%
“…Sweeney, et al 27 reported mortality rates of 3-18%, considering age, perforation time and comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…19 Although Incidence of perforated gastroduodenal peptic ulcer has reduced to 50% over the last 6 years due to the increased use of proton pump inhibitors 20 yet peptic ulcer when perforate still carries high mortality, delay in surgical management is considered a major determinant. 21 The sensitivity and specificity of serology assay varies from 52-94.5%, and 60-97.2% respectively. 22 The biopsy-based methods, on the other hand have a low sensitivity (83%), but a high specificity (100%).…”
Section: Discussionmentioning
confidence: 99%